2006
DOI: 10.4049/jimmunol.176.1.390
|View full text |Cite
|
Sign up to set email alerts
|

Altered Self-Erythrocyte Recognition and Destruction in an Inbred Line of Tilapia (Oreochromis aureus)

Abstract: Carboxyfluorescein diacetate (cFDA)-stained autologous and syngeneic tilapia (Oreochromis aureus) erythrocytes are recognized by effector peripheral blood leukocytes and lysed after a short culture period of 4 h. The hemolysis level was evaluated by measuring the fluorescence of the released cFDA. The degree of lysis of stained target erythrocytes of 60 individuals revealed a trimodal distribution statistically stratified into three groups of low (LR), intermediate (IR), and high (HR) responders. Depletion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Forty‐four normal full‐sibs of the same developmental stage were also fixed in alcohol for comparison in order to examine the possible association between twinning incidences and specific markers. Five of the seven microsatellite markers (UNH101, 148, 159, 187 and 190), which were previously shown to amplify polymorphic products in BIU‐1 inbred line (Shirak et al , 2006) were polymorphic in both parents and, therefore, were used for the twinning analysis in this study. In order to verify the difference in genotypic segregation for UNH159, additional 84 samples of normal full‐sibs were genotyped with this marker.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty‐four normal full‐sibs of the same developmental stage were also fixed in alcohol for comparison in order to examine the possible association between twinning incidences and specific markers. Five of the seven microsatellite markers (UNH101, 148, 159, 187 and 190), which were previously shown to amplify polymorphic products in BIU‐1 inbred line (Shirak et al , 2006) were polymorphic in both parents and, therefore, were used for the twinning analysis in this study. In order to verify the difference in genotypic segregation for UNH159, additional 84 samples of normal full‐sibs were genotyped with this marker.…”
Section: Methodsmentioning
confidence: 99%
“…Palti et al (2002) reported genetic markers that were associated with deleterious effects in a meiogynogenetic tilapia line (BIU‐1). In this gynogenetic line, the number of polymorphic microsatellite markers gradually decreased from 76 in the original stock to 20, 11 and seven in the third, fourth and fifth generations, respectively (Palti et al , 2002; Shirak et al , 2006). By examining dozens of morphological and immunological traits for variability in this line, high uniformity was observed.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Based on a linkage map of 525 microsatellite loci available from Oreochromis niloticus [45], a subset of 169 microsatellite loci were selected. These microsatellites are all dinucleotide repeats of the type (CA) n and have been successfully cross-species amplified in other cichlid studies [46], [47]. Assuming that the location of the loci on the chromosomes is similar in Pelvicachromis and O. niloticus , loci were chosen from different chromosomes in order to assure representative coverage of the whole genome.…”
Section: Methodsmentioning
confidence: 99%